Dielectric ceramic powder and preparation method thereof
Preparation of aggressive ceramic powder through the solution combustion method and chemical deposition method, solving the problem of unstable dielectric performance in high temperature environments and high dielectric loss, realized high energy storage density and good preparation technology, optimized the dielectric ceramic powder powder, Performance and process.
Patent Information
- Application Number
- CN202411227828.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Dielectric ceramic powder has unstable dielectric properties, high dielectric loss, relatively low energy storage density in high temperature environments, and the existing preparation processes have problems such as large particle size, poor stability and high cost.
Dielectric ceramic powder is prepared using solution combustion method and chemical deposition method. Carbon-containing powder is obtained through mixing titanium-based raw materials and organic dispersants, acid adjustment treatment, heating reaction and solvothermal reaction, and dielectric ceramic powder is obtained through calcination. . This method optimizes the combustion reaction, reduces the formation of impurities, and improves dielectric properties by controlling the amounts of glycine and citric acid.
The high-temperature stability, low dielectric loss, and high energy storage density of dielectric ceramic powder are achieved, and the preparation process is optimized to improve the composition uniformity and structural compactness of the finished product.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dielectric ceramic preparation, and in particular relates to dielectric ceramic powder and a preparation method thereof. Background Art
[0002] Dielectric ceramic powders are a class of inorganic powder materials with high dielectric constants and specific dielectric properties. They are usually composed of oxides, non-oxides or their composites, such as titanates, alumina, zirconia, etc. Dielectric ceramic powders play an important role in the fields of electronics, power and communications because they can affect the propagation of electromagnetic waves, store charges, and are used as dielectrics in a variety of electronic devices.
[0003] For example, capacitors made from it can store charge in electronic circuits and be used for functions such as decoupling, filtering and timing control. As a dielectric material for microwave frequency band circuits, dielectric ceramic powders are used to make resonators, filters, dielectric substrates, dielectric antennas and dielectric waveguide circuits, which are widely used in communication equipment and radar systems. At the same time, the high insulation resistivity and good thermal stability of dielectric ceramic powders make them suitable for making insulating supports for current-carrying conductors and various circuit substrates, ensuring electrical isolation and signal integrity between electronic components.
[0004] Although dielectric ceramic powders have many excellent properties, they also have some defects. From a composition perspective, the dielectric constant of common barium titanate-based ceramic powders fluctuates greatly at high temperatures, limiting the application of this material in the field of high-temperature energy storage. Under high-temperature conditions, the lattice vibration inside the dielectric ceramic powder material intensifies, resulting in a decrease in the original electric dipole orientation ability, which will affect the stability of the dielectric constant; thermal excitation increases the probability of electron transitions, resulting in increased energy dissipation and increased dielectric loss; causing changes in the internal structure of the material, resulting in lattice defects and crystal phase transitions, weakening the dielectric strength of the material. Working in a high-temperature environment for a long time, the dielectric ceramic powder material will experience lattice distortion, phase separation and aging, affecting the stability of the dielectric properties of the material. From a process perspective, there are currently two common preparation methods for dielectric ceramic powders: the solid-phase method and the liquid-phase method. Although the existing solid-phase method is simple in process and low in cost, the dielectric ceramic powder obtained has defects such as large particle size and poor stability. When used subsequently, it requires a high temperature for sintering and it is difficult to effectively ensure the uniformity of the composition. Although the liquid-phase method can prepare high-performance powders with small particle size and uniform composition and structure, the overall process is more complicated, the construction period is longer, and it is easy to introduce defects such as organic impurities.
[0005] Therefore, it is urgent to develop a high-performance dielectric ceramic powder and a corresponding method for effectively preparing the high-performance dielectric ceramic powder. Summary of the invention
[0006] In order to solve the problems of dielectric ceramic powder such as unstable dielectric properties, high dielectric loss, relatively low energy storage density when working at high temperature, and certain defects in existing preparation processes, the present invention proposes a dielectric ceramic powder and a preparation method thereof.
[0007] The objects of the present invention are:
[0008] 1. Improve dielectric ceramic powder to ensure high breakdown field strength and good dielectric performance stability of dielectric ceramic products;
[0009] 2. Reduce the dielectric loss of dielectric ceramic powder and increase its energy storage density;
[0010] 3. Effectively optimize the existing dielectric ceramic powder preparation process to form a new and efficient preparation method.
[0011] To achieve the above objectives, the present invention adopts the following technical solutions.
[0012] A method for preparing dielectric ceramic powder,
[0013] The method comprises:
[0014] 1) Mix the titanium-based raw material and the organic dispersant evenly, add acid treatment, then add metal nitrate and the complexing agent, mix evenly, and heat to react to obtain a carbon-containing powder;
[0015] 2) The carbon-containing powder is mixed with metal nitrate and carboxylate derivatives, added to a dispersant and mixed evenly, and then subjected to solvent thermal reaction, filtered, washed, dried and calcined in sequence to obtain dielectric ceramic powder.
[0016] As a preference,
[0017] Step 1) The titanium-based raw material is butyl titanate;
[0018] Step 1) The organic dispersant is ethanol, and its usage is 15-20 mL / mL titanium-based raw material.
[0019] As a preference,
[0020] Step 1) During the acid adjustment process, a nitric acid aqueous solution with a concentration of 6 to 7 mol / L is added;
[0021] The amount of the nitric acid aqueous solution is 2-5 mL / mL of the titanium-based raw material.
[0022] As a preference,
[0023] Step 1) the metal nitrate is strontium nitrate, and its usage is 1.15-1.20 g / mL titanium-based raw material;
[0024] Step 1) the complexing agent is glycine and citric acid;
[0025] The glycine dosage is 6.2-8.0 g / mL titanium-based raw material;
[0026] The amount of citric acid used is 0.5-1.5 wt % of glycine.
[0027] As a preference,
[0028] Step 1) The heating reaction is to heat until foaming but not boiling, and combustion occurs on the liquid surface during the heating process until the solution is completely dried to obtain carbonaceous powder.
[0029] As a preference,
[0030] Step 2) the metal nitrate is a mixture of bismuth nitrate, zirconyl nitrate and aluminum nitrate;
[0031] The bismuth nitrate, zirconyl nitrate and aluminum nitrate are mixed in a molar ratio of 1: (1.05-1.15): (0.95-1.05);
[0032] The bismuth nitrate, zirconium oxynitrate and aluminum nitrate used can be replaced by their hydrates in equal molar amounts. For the raw materials used in the specific experimental research and development of the technical solution of the present invention, the bismuth nitrate used is bismuth nitrate pentahydrate (Bi(NO3)3·5H2O, molar mass 485.07 g / mol), the zirconium oxynitrate is hydrated zirconium oxynitrate (ZrO(NO3)2·xH2O, purchased from Sigma-Aldrich, product serial number MFCD00149896, molar mass 231.23 g / mol), and the aluminum nitrate is aluminum nitrate nonahydrate (Al(NO3)3·9H2O, molar mass 375.13 g / mol);
[0033] The amount of the metal nitrate is 2.2 to 2.4 g / mL of the titanium-based raw material;
[0034] Step 2) the carboxylate derivative is a mixture of sodium oxalate and niobium oxalate;
[0035] The sodium oxalate and niobium oxalate are mixed in a mass ratio of 1:(2.70-2.75);
[0036] The amount of the carboxylate derivative is 0.7 to 0.8 g / g of metal nitrate;
[0037] Step 2) The dispersant is water, and the amount used is 35-38 mL / mL of titanium-based raw material.
[0038] As a preference,
[0039] Step 2) The solvothermal reaction is carried out at a constant temperature of 160 to 180°C for 22 to 24 hours.
[0040] As a preference,
[0041] Step 2) The calcination is carried out at a constant temperature of 900-950°C for 1-1.5 hours.
[0042] A dielectric ceramic powder.
[0043] Generally speaking, small-sized dielectric ceramic grains have high breakdown strength and energy storage density because the high energy barrier between grain boundaries can effectively inhibit the migration of carriers. However, the sintering time of this material is long, which easily causes the loss of volatile elements, uneven composition, excessive grain growth and other problems. To solve this problem, the present invention adopts solution combustion method, chemical deposition method and other methods for preparation.
[0044] In the technical solution of the present invention, a carbon-containing powder is first prepared. The present invention evenly disperses butyl titanate in anhydrous ethanol, adds excess nitric acid for acid adjustment and dissolves the alcoholysis product of butyl titanate in the ethanol system to form TiO(NO3)2, and simultaneously stimulates hydrolysis and dissolution of the hydrolysis product. This is different from directly using a water system. The monomers of the hydrolysis product of the water system are easily contacted to form cross-links, which easily form larger continuous foam products in the subsequent combustion reaction. In the anhydrous ethanol system, since the hydrolysis process is limited and affected by the alcoholysis complex, it will promote the high dispersion of titanium in the reaction system and change the form of the combustion product. However, in this process, the amount of glycine used relative to the titanium-based raw material will significantly affect the actual reaction results. For example, in the case of insufficient glycine, the solution is heated to before the combustion reaction, such as Ti 4+Ions and other metal ions will hydrolyze to produce TiO2, resulting in a decrease in the number of metal ions participating in the combustion reaction and the formation of side reactions, that is, the appearance of more metal oxide impurities, and the solution is more likely to boil and splash during the heating process, so there will be no combustion reaction or only a small amount of combustion reaction. Therefore, in order to reduce the phenomenon of metal nitrate decomposition and gas generation during the heating process, which causes the solution to splash, sufficient glycine is needed in the system to further ensure combustion. Experiments have found that when a sufficient amount of glycine is added, the heated solution does not splash, and the solution burns with an open flame after heating for about 20 minutes. The higher reaction temperature causes the particles to crystallize into smaller and dispersed sponge-like foam combustion products. This is because with the increase in the amount of glycine, the stability of the complex is enhanced, the hydrolysis of metal ions and the formation of impurities are reduced. When the molar ratio of butyl titanate to glycine reaches about 9:22, the impurity content reaches a near minimum value and the sponge-like foam combustion product can be obtained by simply shaking out the ultrafine powder material. When glycine is continued to be added, it is usually considered to cause material waste. As shown in previous studies, excessive glycine will not continue to participate in the combustion reaction, but will absorb a certain amount of heat for self-carbonization, resulting in a decrease in the temperature of the reaction system. Generally speaking, this will lead to a decrease in the crystallinity of the product and an increase in the grain boundaries, which is disadvantageous. In addition, due to the excessive amount of glycine fuel, it is very easy to cause a lack of oxygen in the reaction space, resulting in combustion agglomeration and an increase in carbon residue and organic residue. However, for the technical solution of the present invention, it is necessary to further increase the amount of glycine to ensure that an ultrafine powder more suitable for subsequent treatment is formed, and at the same time, the present invention needs to change the organic dispersion system using anhydrous ethanol, which can change the combustion form, and change the liquid surface combustion from the overall combustion of the solution, thereby greatly improving the degree of combustion, reducing carbon and organic residues and avoiding the occurrence of combustion agglomeration, and directly obtaining ultrafine multi-grain boundary powder, and secondly, because the overall combustion is changed to liquid surface combustion, the combustion ignition time can be shortened, the sufficiency of combustion is improved, the reaction rate is accelerated, and the cross-linking of hydrolysis products is avoided to form smaller crystals and more grain boundaries, and the target ABO3 ultrafine powder product is directly obtained instead of a loose sponge foam combustion product.
[0045] On the basis of the above reaction, and also based on the limited effect of glycine on enhancing the stability of the complex, the present invention further adds a small amount of citric acid as an auxiliary complexing agent. Experiments have shown that the solution without citric acid will induce a hydrolysis reaction and form a small amount of white precipitate during the heating process due to the introduction of nitric acid aqueous solution, while after adding citric acid, the light yellow clear solution is maintained to reduce or even completely inhibit the formation of white precipitate, indicating that citric acid can further enhance the thermal stability of the complex and inhibit the cross-linking and agglomeration of hydrolysis products.
[0046] Then, the present invention uses carbon powder as a substrate, adds bismuth nitrate pentahydrate, hydrated zirconium oxynitrate, aluminum nitrate nonahydrate and other salts, the purpose is to dope wide-bandgap Zr at the B position of ABO3 4+ 、Al 3+ , Nb 5+ The slow diffusion effect of metal ions during doping further effectively inhibits grain boundary diffusion and grain growth, which helps to reduce the size of dielectric ceramic powder, thereby obtaining high breakdown strength and energy storage density. For materials with small grain sizes, more grain boundaries can better prevent carrier migration and obtain greater impedance and insulation capabilities. If there is no Zr 4+ 、Al 3+ , Nb 5+ With the doping of ions, the conduction behavior of dielectric ceramics will not be dominated by grain boundaries, which reduces the difficulty of long-range migration of carriers in the material, thus affecting the impedance and insulation capacity of dielectric ceramics, and the narrow band gap is not conducive to improving the breakdown strength of dielectric ceramics. However, in general, it is very difficult to achieve uniform ion levels of multiple metal ions through simple mechanical mixing. If the metal raw materials are not fully contacted, more impurities will be generated. Compared with traditional solid-phase reactions, dielectric ceramics have higher uniformity and phase purity.
[0047] Furthermore, Nb 5+ Ion-assisted dielectric ceramics increase the grain boundary activation energy and grain boundary resistance, inhibit the generation and transmission of carriers, and improve the breakdown strength. 5+ ions are beneficial to reduce the metal diffusion rate during the sintering process. However, during the solvent thermal treatment, Zr 4+ 、Al 3+ , Nb 5+ The average substitution radius of the ions is about 0.65 Å, which is smaller than that of the substituted Ti 4+ The ionic radius (0.605 Å) is large, and adding excessive metal nitrates will cause excessive expansion of the lattice, causing the oxygen octahedron to be distorted, and more by-products are easily produced in this process. In order to avoid the problems of local distortion, the formation of thermodynamically unstable phases and impurity phases, the present invention limits the amount of hydrated zirconium oxynitrate, nonahydrated aluminum nitrate, and niobium oxalate.
[0048] In addition, Na doping at the A site in ABO3 + 、Bi 3+ Ions are conducive to the formation of a small amount of (Sr, Bi, Na)TiO3 inside the dielectric ceramic. This substance has a low melting point and can assist sintering. It is easy to form a sintering liquid phase, thereby inhibiting the growth of grains and facilitating the rapid densification of the dielectric ceramic in the subsequent sintering process. 3+The ions are beneficial to preserve a small residual polarization intensity, and the formed BiAlO3 is beneficial to increase the polarization change (the difference between the polarization intensity and the residual polarization intensity), and appropriately improve the piezoelectric properties of the material. + 、Bi 3+ Ions will produce impurity phases and affect the structure of dielectric ceramics. Therefore, based on the amount of bismuth salt used, the present invention limits the amount of sodium salt used.
[0049] The A and B sites are replaced by ions of different radii, and the ions shift from the original lattice site center, which enhances the relaxation performance of dielectric ceramics. With the increase of temperature, the energy storage performance of dielectric ceramics decays slightly, and the change of free relative dielectric constant is less than 15%, showing good temperature stability of dielectric ceramics. Moreover, dielectric ceramics have a moderate dielectric constant and extremely low dielectric loss tangent at room temperature, which is conducive to obtaining excellent energy storage performance. In addition, with the increase of Al 3+ 、Zr 4+ , Nb 5+ Due to the slow diffusion of plasma, A-site vacancies tend to concentrate at the grain boundaries, forming a pinning effect, which refines the grains of dielectric ceramics. With the synergistic uniform composition and structure, dielectric ceramics have finer and more uniform grains, high chemical uniformity, and a dense structure, achieving higher hardness. Further, the Vickers indentation of dielectric ceramics was characterized, and it was found that the indentation was a symmetrical diamond structure, and the cracks extended in a straight line, indicating that dielectric ceramics have good plasticity and high hardness. These are conducive to ceramic products maintaining good energy storage performance during packaging and transportation, and extending the service life of the material.
[0050] The beneficial effects of the present invention are as follows:
[0051] (1) The dielectric constant of the dielectric ceramic powder of the present invention is adjustable and has excellent high-temperature stability. When working in a high-temperature environment, the products prepared from the dielectric ceramic powder of the present invention can maintain good dielectric properties;
[0052] (2) The product prepared from the dielectric ceramic powder of the present invention has low dielectric loss and high energy storage density;
[0053] (3) The dielectric ceramic powder of the present invention can be sintered to obtain small-sized products, and the small-sized products still have high breakdown field strength, good energy storage performance and dielectric property stability. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0055] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0056] Example 1
[0057] A method for preparing dielectric ceramic powder, the method comprising:
[0058] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 124 g of glycine, and 1.24 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 11 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned and then self-extinguished to obtain carbon-containing powder;
[0059] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0060] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance of the ceramic sample was tested as follows.
[0061] 1. Free relative dielectric constant:
[0062] According to GB / T 3389-2008, the capacitance of the ceramic sample is tested in an electric field environment with an intensity of 3 V / mm and a frequency of 1 kHz, and its free relative dielectric constant is calculated using the following formula.
[0063]
[0064] Where: ε T is the free relative dielectric constant of the test material; C T To detect the free capacitance of the material, F; is the length of the test material, m; ε0 is the dielectric constant of the test material in vacuum; A is the electrode area of the test material, m 2 .
[0065] 2. Dielectric loss tangent value:
[0066] Metal electrode layers were coated on both sides of a clean sample of 9.6 mm × 1.3 mm, and polarization treatment was applied to the polarization electric field. At room temperature, the polarization electrodes were removed, and a metal layer was coated on the 10.0 × 9.6 mm surface as an excitation electrode. The sample was left at room temperature for 2 h, and the dielectric loss tangent was calculated according to GB / T 3389-2008 in an electric field environment with an intensity of 3 V / mm and a frequency of 1 kHz. The calculation formula is as follows.
[0067]
[0068] Where: tan α is the dielectric loss tangent; f i is the value of the fundamental frequency or overtone frequency, Hz; k 15 is the ratio of the overtone frequency to the fundamental frequency of the shear mode of the piezoelectric sample; f p is the parallel resonant frequency, Hz.
[0069] 3. High temperature stability:
[0070] A metal electrode layer was coated on both sides of a clean sample of 9.6 mm × 1.3 mm, and the sample was left to stand at room temperature for 2 h. The dielectric constant of the blank control group ceramic material was measured using an instrument. Furthermore, the control group ceramic material was uniformly heated to 125 ° C, and the dielectric constant of the ceramic material under high temperature conditions was directly measured using an instrument. If the dielectric constant change was less than 15%, the sample was marked as qualified, otherwise it was marked as unqualified.
[0071] 4. Breakdown strength (E b ):
[0072] Wipe the ceramic sample clean, measure the thickness and breakdown voltage of 50 points of the ceramic sample according to GB / T 1408.1-2016, and divide the breakdown voltage of each sample by the thickness to obtain the breakdown field strength.
[0073] 5. Energy storage density (W rec ):
[0074] The hysteresis loop of the sample was tested at room temperature using a Premier II / Radiant tester with a test frequency of 10 Hz.
[0075] The results are shown in Table 1.
[0076] Table 1: Performance test results of samples in Example 1.
[0077]
[0078] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0079] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.997, which shows that the dielectric ceramic powder of the present invention has a very excellent sintering ability, almost no sintering loss and forms a nearly completely dense sintering.
[0080] In this case, sufficient glycine was added, and no splashing occurred during heating. After 20 minutes, the solution bubbled and burned with an open flame. After a series of preparation processes, the sintered ceramic product was characterized, and it was found that the interior showed a perovskite structure with a low content of impurities. According to the results in Table 1, the temperature-related dielectric constant curve is almost a straight line with a gentle slope, indicating that the ceramic sample has good high-temperature stability. Moreover, the ceramic sample has extremely low porosity and uniform composition, and the probability of breakdown at the pores is low. The ceramic sample in this case has a wide energy band gap, which is consistent with the high breakdown field strength in the table. Moreover, the ceramic product has a high energy storage density.
[0081] Example 2
[0082] A method for preparing dielectric ceramic powder, the method comprising:
[0083] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 144 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0084] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0085] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 2.
[0086] Table 2: Performance test results of samples in Example 2.
[0087]
[0088] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0089] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.998, which shows that the dielectric ceramic powder of the present invention has a very excellent sintering ability, almost no sintering loss and forms a nearly completely dense sintering.
[0090] As the amount of glycine increases, the stability of the complex increases, reducing the hydrolysis of metal ions and the formation of impurities. Characterization shows that the material has a single perovskite structure. According to the results in Table 2, the dielectric constant and breakdown field strength of the ceramic product increase, and the higher breakdown strength enables the material to achieve a higher energy storage density.
[0091] In addition, the Vickers indentation of dielectric ceramics was characterized and it was found that the indentation was a symmetrical diamond structure and the cracks extended in a straight line, indicating that the dielectric ceramics have good plasticity and high hardness. These are conducive to maintaining good energy storage performance of ceramic products during packaging and transportation, and extending the service life of the material.
[0092] Example 3
[0093] A method for preparing dielectric ceramic powder, the method comprising:
[0094] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 160 g of glycine, and 1.60 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0095] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0096] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 3.
[0097] Table 3: Performance test results of samples in Example 3.
[0098]
[0099] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0100] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.998, which shows that the dielectric ceramic powder of the present invention has a very excellent sintering ability, almost no sintering loss and forms a nearly completely dense sintering.
[0101] According to the results in Table 3, as the amount of glycine increases further, part of the glycine does not participate in the combustion, but absorbs energy to achieve the decomposition and carbonization of the glycine itself, resulting in a decrease in the system temperature. The particles will not continue to grow, but the particle crystallinity will decrease. Moreover, due to the limited volume ratio of the reaction container, that is, the amount of O2 that instantly enters the reaction container and participates in the reaction during combustion is limited, the reaction is not sufficient, and the crystal crystallinity will obviously decrease.
[0102] In addition, the ceramic sample in this example is loaded with 10 7After testing, it was found that W rec There is almost no attenuation and dielectric ceramics have good fatigue resistance, which is the synergistic result of their uniform composition, low dielectric loss and low dielectric frequency dispersion effect.
[0103] Combined with the results of Examples 1 to 3, it can be seen that the product prepared by the dielectric ceramic powder of the present invention has a moderate dielectric constant and an extremely low dielectric loss tangent at room temperature, and has excellent energy storage performance. The A and B positions in the dielectric ceramic powder (ABO3) are replaced by ions of different radii, and the ions are offset from the original lattice point center, which enhances the relaxation performance of the dielectric ceramic. As the temperature increases, the energy storage performance of the dielectric ceramic is slightly attenuated, and the free relative dielectric constant changes by less than 15%, showing good temperature stability of the dielectric ceramic. The dielectric ceramic powder of the present invention can be used to achieve miniaturization of ceramic products while maintaining dielectric properties, and the miniaturized products still have high breakdown field strength, good energy storage performance and dielectric performance stability.
[0104] Comparative Example 1
[0105] A method for preparing dielectric ceramic powder, the method comprising:
[0106] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 107 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 15 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned and then self-extinguished to obtain carbon-containing powder;
[0107] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0108] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 4.
[0109] Table 4: Performance test results of samples of Comparative Example 1.
[0110]
[0111] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0112] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.992, and the relative density decreased compared with Examples 1 to 3, which indicates that the sintering ability of the dielectric ceramic powder obtained in this example has decreased, which may be related to the relative increase in its particle size, and due to the reduction in the amount of glycine used, the difficulty of doping in the actual subsequent doping process has increased relatively.
[0113] In this case, the amount of glycine used was insufficient. In this case, before the solution was heated to the combustion reaction, some metal ions were hydrolyzed, such as Ti 4+ Ion hydrolysis produces TiO2, which causes more metal oxide impurities to appear during the combustion reaction, resulting in a large number of impurities in the ceramic sample. According to the results in Table 4, although the ceramic sample in this example still maintains low dielectric loss, the dielectric constant is low, and the low breakdown field strength cannot achieve high energy storage performance, so the product has poor applicability.
[0114] Comparative Example 2
[0115] A method for preparing dielectric ceramic powder, the method comprising:
[0116] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate and 144 g of glycine and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0117] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0118] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 5.
[0119] Table 5: Performance test results of samples of Comparative Example 2.
[0120]
[0121] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0122] According to the research of those skilled in the art, the effect of glycine on enhancing the stability of the complex is limited. The solution without the auxiliary complexing agent citric acid is hydrolyzed during heating to form a small amount of white precipitate, and the thermal stability of the complex decreases. According to the results in Table 5, the dielectric constant of the ceramic sample in this example changes by more than 15% under high temperature environment, and its breakdown field strength and energy storage density are reduced.
[0123] Comparative Example 3
[0124] A method for preparing dielectric ceramic powder, the method comprising:
[0125] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid adjustment, add 23 g of strontium nitrate, 144 g of glycine and 1.44 g of citric acid and mix evenly to obtain a mixed solution A;
[0126] 2) Take another 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water and mix them evenly to obtain a mixed solution B. Mix the mixed solutions A and B, keep the mixture at 160 °C for 24 h, and separate the solids after filtration. Wash the solids with deionized water and dry them at 60 °C. Keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0127] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 6.
[0128] Table 6: Performance test results of samples of comparative example 3.
[0129]
[0130] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0131] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.979, which was lower than that of Examples 1 to 3, indicating that the sintering difficulty of the dielectric ceramic powder obtained in this example was significantly increased, and a longer sintering time was required to effectively achieve densification.
[0132] This example only uses simple mechanical mixing, but the metal ions fail to reach uniform ion levels and fail to fully contact, resulting in more impurities, poor uniformity and low phase purity of the dielectric ceramic. Moreover, the theoretical sintering time of this material is relatively long. After characterization, it is found that the material in this example has problems of uneven composition and excessive grain growth. Compared with Example 2, the grain size of the dielectric ceramic is larger. According to the results in Table 6 above, the dielectric ceramic has lower breakdown strength and energy storage density. It can be seen that the solution combustion method plays a key role.
[0133] Comparative Example 4
[0134] A method for preparing dielectric ceramic powder, the method comprising:
[0135] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 144 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0136] 2) Add 19.6 g of bismuth nitrate pentahydrate, 8.4 g of sodium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0137] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 7.
[0138] Table 7: Performance test results of samples of Comparative Example 4.
[0139]
[0140] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0141] From the results in Table 7, the B position in the dielectric ceramic powder ABO3 in this example is not doped with wide bandgap metal ions, and its grain boundary diffusion speed is faster and the size is larger than that in Example 2. At the same time, due to the absence of wide bandgap metal ion doping, the conduction behavior of the dielectric ceramic is not dominated by the grain boundary, which reduces the difficulty of long-range migration of carriers in the material, which is manifested in the lower breakdown strength and poorer dielectric properties of the dielectric ceramic.
[0142] Comparative Example 5
[0143] A method for preparing dielectric ceramic powder, the method comprising:
[0144] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 144 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0145] 2) Add 19.6 g of bismuth nitrate pentahydrate, 11.0 g of hydrated zirconium oxynitrate, 16.5 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 24.5 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0146] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surfaces were parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 8.
[0147] Table 8: Performance test results of samples of comparative example 5.
[0148]
[0149] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0150] In this example, excessive amounts of hydrated zirconium oxynitrate, aluminum nitrate nonahydrate, and niobium oxalate were added, resulting in excessive expansion of the lattice, distortion of the oxygen octahedron, and the generation of more byproducts, forming thermodynamically unstable phases and impurity phases. According to the results in Table 8, not only the dielectric properties of the dielectric ceramics are reduced, but also the high temperature stability is significantly deteriorated.
[0151] Comparative Example 6
[0152] A method for preparing dielectric ceramic powder, the method comprising:
[0153] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 144 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and the liquid surface is ignited after about 10 minutes of foaming, and the combustion reaction starts from the liquid surface until the solution is completely burned out and then self-extinguished to obtain carbon-containing powder;
[0154] 2) Add 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 22.7 g of niobium oxalate and 700 mL of water to the carbon-containing powder, mix well, keep the mixture at 160 °C for 24 h, separate the solid matter by filtration, wash the solid matter with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0155] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surfaces were parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 9.
[0156] Table 9: Performance test results of samples of comparative example 6.
[0157]
[0158] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0159] In this example, the A position of the dielectric ceramic powder ABO3 is not doped with Na + 、Bi 3+ ions, failed to form low-melting-point (Sr, Bi, Na)TiO3, the effect of liquid phase sintering became worse, and characterization found that the grain size of the ceramic sample was larger. Larger grains reduce the number of grain boundaries, making it easier for carriers to pass through the grain boundaries, resulting in reduced dielectric properties, and the material is not conducive to the preparation of miniaturized products.
[0160] In addition, the ceramic samples of Comparative Examples 4 and 6 were characterized. Combined with the results in Table 2, Table 7 and Table 9 of Example 2, Comparative Example 4 and Comparative Example 6, as Al 3+ 、Zr 4+ , Nb 5+ Due to the slow diffusion of plasma, the A-site vacancies in the dielectric ceramic powder (ABO3) tend to concentrate at the grain boundary, forming a pinning effect, which makes the dielectric ceramic grains finer. With uniform composition and structure, the dielectric ceramic has finer and more uniform grains, high chemical uniformity, and a dense structure, achieving higher hardness.
[0161] Comparative Example 7
[0162] A method for preparing dielectric ceramic powder, the method comprising:
[0163] 1) Take 20 mL of butyl titanate and 300 mL of water and mix them evenly. Add 40 mL of 6 mol / L nitric acid to adjust the acid and dissolve the white precipitate. Add 23 g of strontium nitrate, 144 g of glycine and 1.44 g of citric acid and mix them evenly. Heat until the solution foams and the solution is ignited as a whole after foaming for about 20 min. After the solution is completely dried up, it extinguishes itself to obtain a sponge-like combustion product. Place it on an ultrasonic test bench and ultrasonically disperse it to obtain a carbon-containing powder.
[0164] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0165] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surfaces were parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 10.
[0166] Table 10: Performance test results of samples of comparative example 7.
[0167]
[0168] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained.
[0169] In addition, the relative density of the ceramic sample obtained by sintering in this example was characterized, and the relative density = (density of the ceramic sample in this example / density of the dielectric ceramic powder in this example) × 100%. After characterization, the relative density of the ceramic sample obtained in this example reached 0.986. According to Table 10, compared with the previous embodiment, this example only changed the solvent system of the dispersion system in step 1), but it had a very significant impact on the product performance. This is because the combustion form was changed, and the hydrolysis-alcoholysis balance in the system was destroyed, resulting in an increase in the powder particle size and an increase in the crystallinity of the carbon-containing powder. Although the powder obtained in the end still has relatively good basic performance, it is not suitable for ion doping in subsequent steps, resulting in a decrease in performance.
[0170] Comparative Example 8
[0171] A method for preparing dielectric ceramic powder, the method comprising:
[0172] Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly. Add 40 mL of 6 mol / L nitric acid for acid treatment. Add 23 g of strontium nitrate and 1.44 g of citric acid and mix them evenly. Heat until the solution foams and does not burn after 30 minutes of foaming.
[0173] Since the combustion process cannot occur, the desired intermediate cannot be obtained, making it difficult to proceed to the subsequent preparation steps.
[0174] This indicates that the addition of glycine is a crucial "fuel" component for the combustion self-extinguishing process to be achieved by the technical solution of the present invention.
[0175] Comparative Example 9
[0176] A method for preparing dielectric ceramic powder, the method comprising:
[0177] 1) Take 20 mL of butyl titanate and 300 mL of ethanol and mix them evenly, add 40 mL of 6 mol / L nitric acid for acid treatment, add 23 g of strontium nitrate, 10.4 g of glycine, and 1.44 g of citric acid and mix them evenly, heat until the solution foams and ignites after foaming for about 21 minutes, and the part of the solution close to the liquid surface begins to burn until the solution is completely dried and then self-extinguished to obtain a sponge-like foam combustion product, which is shaken off to obtain a carbon-containing powder;
[0178] 2) Add 19.6 g of bismuth nitrate pentahydrate, 9.8 g of hydrated zirconium oxynitrate, 14.7 g of aluminum nitrate nonahydrate, 8.4 g of sodium oxalate, 22.7 g of niobium oxalate, and 700 mL of water to the carbon-containing powder, mix well, and keep the mixture at 160 °C for 24 h. After filtering, separate the solid, wash the solid with deionized water, dry it at 60 °C, and keep the mixture at 950 °C for 1 h to obtain dielectric ceramic powder.
[0179] 100 g of the dielectric ceramic powder prepared in this example and 5 g of polyvinyl alcohol were mixed and granulated uniformly. A pressure of 300 MPa was vertically applied to form a ceramic green body with a size of 10.0×9.6 mm×1.3 mm. The green body was kept at 650°C for 2 h for debinding, and the temperature was increased to 1300°C and kept for 2 h. After cooling, the green body was polished until the surface was parallel to obtain a ceramic sample. The performance test of the ceramic sample was carried out in the same manner as in Example 1. The results are shown in Table 11.
[0180] Table 11: Performance test results of samples of comparative example 9.
[0181]
[0182] According to the above table, the basic performance characterization values of the samples prepared in this example can be obtained. Since the product of this example is an early R&D sample and the sample is lost, only part of the above data and experimental operation records are retained, among which the operation process of step 1) has been re-verified and meets the records.
[0183] It can be clearly seen from the characterization results in Table 11 that the amount of glycine used in this example is insufficient. In this case, before the solution is heated to the combustion reaction, there is ion hydrolysis to produce metal oxides, resulting in the appearance of metal oxide impurities during the combustion reaction. In addition, the dielectric constant of the ceramic sample in this example is low, the dielectric loss is relatively large, and the applicability is poor. In addition, the combustion form shown in the experimental process of step 1) is also obviously different. It will also spread and burn to a certain range below the liquid level in the ethanol system. The form and morphology of the obtained product are also significantly different from the aforementioned Examples 1 to 3. This example, Example 2, Comparative Example 2 and Comparative Example 8 together show that glycine plays a crucial role in the preparation process of the technical solution of the present invention. First, it affects whether the combustion reaction can be carried out. Secondly, its amount also significantly affects the form of combustion and the morphology and specific composition of the product obtained in step 1) after the combustion reaction. The specific composition affects the subsequent preparation steps and ultimately affects the performance. Therefore, the present invention also needs to control the amount of glycine relatively effectively.
Claims
1. A method for preparing dielectric ceramic powder, characterized in that: The method comprises: 1) A titanium-based raw material is mixed evenly with an organic dispersant, and then an acid treatment is performed. A metal nitrate and a complexing agent are then added, mixed evenly, and heated to react to obtain a carbon-containing powder; 2) mixing the carbonaceous powder with the metal nitrate and carboxylate derivatives into a dispersant and mixing them evenly, performing a solvent thermal reaction, and then filtering, washing, drying and calcining in sequence to obtain a dielectric ceramic powder; Step 1) The titanium-based raw material is butyl titanate; Step 1) the organic dispersant is ethanol, and the amount thereof is 15-20 mL / mL titanium-based raw material; Step 1) the metal nitrate is strontium nitrate, and its usage is 1.15-1.20 g / mL titanium-based raw material; Step 1) the complexing agent is glycine and citric acid; The glycine dosage is 6.2-8.0 g / mL titanium-based raw material; The amount of citric acid is 0.5-1.5 wt% of glycine; Step 1) The heating reaction is heated until foaming but not boiling, and the liquid surface is burned during the heating process until the solution is completely dried to obtain carbonaceous powder; Step 2) the metal nitrate is a mixture of bismuth nitrate, zirconyl nitrate and aluminum nitrate; The bismuth nitrate, zirconyl nitrate and aluminum nitrate are mixed in a molar ratio of 1: (1.05-1.15): (0.95-1.05); The amount of the metal nitrate is 2.2 to 2.4 g / mL of the titanium-based raw material; Step 2) the carboxylate derivative is a mixture of sodium oxalate and niobium oxalate; The sodium oxalate and niobium oxalate are mixed in a mass ratio of 1:(2.70-2.75); The amount of the carboxylate derivative is 0.7 to 0.8 g / g of metal nitrate; Step 2) The dispersant is water, and the amount used is 35-38 mL / mL of titanium-based raw material.
2. The method for preparing a dielectric ceramic powder according to claim 1, characterized in that: Step 1) During the acid adjustment process, a nitric acid aqueous solution with a concentration of 6 to 7 mol / L is added; The amount of the nitric acid aqueous solution is 2-5 mL / mL of the titanium-based raw material.
3. The method for preparing a dielectric ceramic powder according to claim 1, characterized in that: Step 2) The solvothermal reaction is carried out at a constant temperature of 160 to 180°C for 22 to 24 hours.
4. The method for preparing a dielectric ceramic powder according to claim 1, characterized in that: Step 2) The calcination is carried out at a constant temperature of 900-950°C for 1-1.5 hours.
5. A dielectric ceramic powder obtained by the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of strontium titanate energy storage dielectric ceramic material with high breakdown and high energy storage density
CN112279639A
High-temperature stable sodium bismuth titanate-strontium titanate-based dielectric energy storage ceramic material as well as preparation and application thereof
CN114716243A
Method for preparing crystalline state perovskite compounds powder
CN1524792A